A new strategy for the controllable growth of MOF@PBA architectures. Issue 29 (12th July 2019) - Xiao, Xiao; Zhang, Guangxun; Xu, Yuxia; Zhang, Hualin; Guo, Xiaotian; Liu, Yong; Pang, Huan
Abstract : Multilevel nanostructures can expose more active sites and promote the charge transfer process, and different composite materials can promote the synergistic effect. Abstract : Presently, it is a substantial challenge to fabricate ordered multilevel nanostructures by simple methods. Herein, we successfully combined 1D MOF ultrathin nanobelts with PBA nanocubes via an in situ cation exchange strategy to synthesize a series of 3D multilevel MOF@PBA hybrid materials (Ni-MIL-77@PBA, NiCo-MOF@PBA, NiMn-MOF@PBA, and NiCoMn-MOF@PBA). In addition to these improvements, we extended the in situ cation exchange strategy to 2D MOF nanosheet assembles and 3D MOF polyhedra, which combine perfectly with PBA nanocubes to form new MOF@PBA architectures. The obtained MOF@PBA architectures exhibit an efficient catalytic oxygen evolution ability under strongly alkaline conditions. Therefore, the synthesis strategy of this study opens up a new way to construct other modified hybrid materials and has broad application prospects.